DAKWAH DAN MUSIK: - Akhmad Zaini (LP2M Universitas Ibrahimy, 2014)
Rhoma Irama is One of the poplar musicians are interesting to study. Here are two things; firstly, Rhoma Irama as unique person, especially the Islamic identity. Second, Rhoma Irama as the development of Indonesian dangdut music. This study to describe Rhoma Irama as the phenomenon and dangdut. As a Muslim, he is a personal who want to practice her faith as understood consequently. Islam as a way of life and his identity and a make it to be a sing’s content. On the other side, Rhoma Irama is a musician, and musician, dangdut as his choice. It will also answer the question Rhoma Irama as two different side, Da'wah and Music.